DEVELOPMENT OF ALGORITHM OF SMART GEOGRAPHIC AREA - Yusifov S.I; Ragimova N.A; Abdullayev V.H; Khalilov M.E (EKSAKTA: Journal of Sciences and Data Analysis, 2021)
The rapid development of information technologies accelerates the approximations of industry 4.0, which is why sectors of the economy and science must adapt to these changes. Global changes in geography have led to the emergence of a new scientific discipline called geoinformatics. It then provides insight into the Smart Geographic Area, its structure and the main components. To do this, there used methods for communicating the main components IIoT, IoE), for analyzing data (Big Data, Hadoop), for managing processes (CPs), for storing data (Cloud Computing, Fog Computing). As a result of the study, there was developed a Smart Geographic Area algorithm based on the MapReduce paradigm.